Holographic deconfinement transition in the presence of a magnetic field - Ballon-Bayona, Alfonso (Springer, 2013)
We investigate the thermodynamics of the flavour sector of the Sakai-Sugimoto model in the presence of a magnetic field. Renormalizing the euclidean Dirac-Born-Infeld action in the antipodal limit, we find for the con fined and deconfined phases positive contributions to the pressures that grow with the magnetic field. We also obtain positive magnetic susceptibilities indicating a paramagnetic behaviour of quarks. Using these results we estimate a lambda(2)/N-c correction to the deconfinement temperature that decreases as a function of the magnetic field.
Keywords: Gauge-gravity correspondence; Holography and quark-gluon plasmas